Characteristics of South African firms that hedge against foreign exchange risk - Arnold, Katherine (My University, 2012)
Increased globalisation of international business and operations results in an increase of firms facing foreign exchange risk. One of the ways to mitigate this risk is the use of currency derivatives to hedge this foreign exchange exposure. This research explores the characteristics of South African firms that use currency derivatives in contrast to those that do not. The data is collected and calculated from financial statement of firms listed on the main board of the JSE. The variables are tested using t-tests to accept or reject the hypothesis. There are five characteristics which are tested, level of foreign exchange exposure, firm size, propensity to bankruptcy, underinvestment in growth opportunities and level of managerial ownership. The findings for the theories on bankruptcy costs and managerial ownership affecting a firm’s decision to hedge are consistent with previous literature indicating that these characteristics are not significant in determining a firm’s policy on hedging. The literature also supports the test results for the theory on firm size and level of foreign exposure, stating that the larger firms and those with higher levels of foreign exposure are more likely to hedge their foreign exchange risk with the use of currency derivatives. In conflict with international trends high growth opportunities is not seen as significant within the South African context. The key finding is that firm size and level of foreign exchange are the prominent characteristics in the South African context when describing whether a firm will hedge it’s foreign exchange exposure with currency derivatives or not
MBA thesis - WBS
Keywords: Foreign exchange risk; Derivatives; Hedge funds